Web Engineering 10th International Conference, ICWE 2010, Vienna Austria, July 5-9, 2010. Proceedings - Benatallah, Boualem; Casati, Fabio; Kappel, Gerti; Rossi, Gustavo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 10th International Conference on Web Engineering, held in Vienna, Austria, in July 2010.
Search -- Searching Repositories of Web Application Models -- Toward Approximate GML Retrieval Based on Structural and Semantic Characteristics -- Advancing Search Query Autocompletion Services with More and Better Suggestions -- Designing Service Marts for Engineering Search Computing Applications -- Web Services -- Engineering Autonomic Controllers for Virtualized Web Applications -- AWAIT: Efficient Overload Management for Busy Multi-tier Web Services under Bursty Workloads -- Normative Management of Web Service Level Agreements -- Combining Schema and Level-Based Matching for Web Service Discovery -- Web Messaging for Open and Scalable Distributed Sensing Applications -- On Actors and the REST -- Development Process -- Multi-level Tests for Model Driven Web Applications -- Capture and Evolution of Web Requirements Using WebSpec -- Re-engineering Legacy Web Applications into Rich Internet Applications -- Deriving Vocal Interfaces from Logical Descriptions in Multi-device Authoring Environments -- Quality, Quality in Use, Actual Usability and User Experience as Key Drivers for Web Application Evaluation -- Interfaces for Scripting: Making Greasemonkey Scripts Resilient to Website Upgrades -- Web 2.0 -- Context-Aware Interaction Approach to Handle Users Local Contexts in Web 2.0 -- Rethinking Microblogging: Open, Distributed, Semantic -- A Web-Based Collaborative Metamodeling Environment with Secure Remote Model Access -- Carbon: Domain-Independent Automatic Web Form Filling -- Scalable and Mashable Location-Oriented Web Services -- Linked Data -- A Flexible Rule-Based Method for Interlinking, Integrating, and Enriching User Data -- Ranking the Linked Data: The Case of DBpedia -- Linkator: Enriching Web Pages by Automatically Adding Dereferenceable Semantic Annotations -- Performance and Security -- A Generic Proxy for Secure Smart Card-Enabled Web Applications -- Efficient Term Cloud Generation for Streaming Web Content -- Industry Papers -- Experiences in Building a RESTful Mixed Reality Web Service Platform -- WebRatio BPM: A Tool for Designing and Deploying Business Processes on the Web -- A Visual Tool for Rapid Integration of Enterprise Software Applications -- Customization Realization in Multi-tenant Web Applications: Case Studies from the Library Sector -- Challenges and Experiences in Deploying Enterprise Crowdsourcing Service -- Business Conversation Manager: Facilitating People Interactions in Outsourcing Service Engagements -- Demo and Poster Papers -- Tools for Modeling and Generating Safe Interface Interactions in Web Applications -- Linking Related Documents: Combining Tag Clouds and Search Queries -- GAmera: A Tool for WS-BPEL Composition Testing Using Mutation Analysis -- Open, Distributed and Semantic Microblogging with SMOB -- The ServFace Builder - A WYSIWYG Approach for Building Service-Based Applications -- Extracting Client-Side Web User Interface Controls -- Applying Semantic Web Technology in a Mobile Setting: The Person Matcher -- Syncro - Concurrent Editing Library for Google Wave -- An Eclipse Plug-in for Model-Driven Development of Rich Internet Applications -- A Cross-Platform Software System to Create and Deploy Mobile Mashups -- A Blog-Centered IPTV Environment for Enhancing Contents Provision, Consumption, and Evolution -- Factic: Personalized Exploratory Search in the Semantic Web -- Takuan: A Tool for WS-BPEL Composition Testing Using Dynamic Invariant Generation.
Keywords: Computer science; Computer Communication Networks; Database management; Data mining; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Database Management; Computer Communication Networks; Data Mining and Knowledge Discovery